VD_FINDINFO 73/2017/PHC vom 18. Oktober 2017 - VD Tribunal cantonal (2017)
INSTANCE UNIQUE, MESURE PROVISIONNELLE, CONCURRENCE DÉLOYALE, RISQUE DE CONFUSION | 3 al. 1 let. b LCD, 3 al. 1 let. d LCD, 261 CPC (CH), 5 CPC (CH)